Analisis Strategi Pengembangan Usaha Kripik Singkong ”Gunung Kawi Malang” di Desa Andongsari Kecamatan Ambulu Kabupaten Jember - Lestari, Puji Dwi; Hawa, Tidar Aden (Program Studi Agribisnis, 2021)
Agro-industry is one of the sectors capable of increasing the income of agribusiness actors. The cassava chips business in Gunug Kawi Malang is one of the cassava agro-industries located in Andongsari Village, Ambulu District, Jember Regency. The purpose of this study was to look at internal and external factors in the Gunung Kawi Malang chips business and to see what alternative strategies were suitable for the Gunung Kawi Malang chips business. This study uses the method of Internal Matrix Analysis (IFE) and External Matrix (EFE) to see what factors exist within the company (strengths and weaknesses) or those outside the company (opportunities and threats), Internal External Matrix (IE). how the company works and the SWOT matrix to develop alternative strategies that will be used for the company. From the research results, there are 10 internal factors of the company, while for the external factors of the company there are 10 factors. From the results of the IE matrix, it shows that the business rank of Gunung Kawi Malang cassava chips is in cell V, namely guard and maintain. Keywords: Pengembangan; Faktor Internal dan Eksternal; Alternatif Strategi.